Microstructure and magnetoresistance of sputtered bismuth thin films upon annealing - Chang, J; Kim, H; Han, J; Jeon, MH; Lee, WY (AMER INST PHYSICS, 2005)
We investigated the microstructure and magnetotransport properties of sputtered Bi upon annealing. The grain size and the orientation of polycrystalline Bi thin films can be manipulated through a proper annealing treatment. Weak-oriented fine grains, of which size is about 0.1 mu m, were found in as-sputtered Bi films. Careful annealing at 270 degrees C results not only in a grain growth of up to 1.1 mu m but also in a [001]-preferred orientation structure. The grain size increases exponentially with annealing time in the temperature range of 266-270 degrees C. The grain-growth exponent (n) and the activation energy (Q) were evaluated to be 0.32 +/- 0.05 and 70.7 kJ/mol, respectively. The magnetoresistance (MR) of Bi films is strongly dependent on the microstructure and thickness of the film, and on the measured temperature. A very high MR of 30,000% can be observed in the annealed 7-mu m-thick Bi films when measured at low temperature (4 K). The drastic increase in MR after annealing is largely attributed to the trigonal-axis-oriented texture diminishing anisotropy scattering as well as to the significant grain-growth decreasing grain-boundary scattering of carriers. The measured temperature and film thickness on which the phonon scattering relies are also important factors in determining the magnetoresistance of sputtered Bi films. (c) 2005 American Institute of Physics.
Keywords: DIFFUSION; GROWTH